Factors Influencing Transportation Mode Preferences for Educational Trips Among Dormitory Resident University Students in Kütahya, Türkiye - Peker, Raziye; Yardim, Mustafa Sinan; Akalin, Kadir Berkhan (MDPI, 2024)
This study explores the transportation behaviors of university students residing in dormitories in K & uuml;tahya, T & uuml;rkiye, emphasizing their preferred modes for educational trips. Utilizing a Multinomial Logit model, the research analyzes the influence of socio-demographic factors, trip characteristics, and environmental perceptions on mode choice. The results indicate that public transport and walking are the predominant modes, with significant negative associations being observed between car ownership and the likelihood of choosing these sustainable options. Key findings reveal that, as trip distances increase, students are more likely to use public transport, while higher income levels decrease reliance on both public transport and walking. Male students demonstrate a higher preference for these modes compared to female students. Environmental perceptions, including feelings of safety and satisfaction with infrastructure, play a critical role in shaping transportation choices, highlighting the need for improved lighting, walkability, and public transport quality. These insights have important implications for transportation policy, suggesting that reducing private vehicle reliance and enhancing public transport services can significantly promote sustainable travel behaviors. Overall, the study underscores the importance of comprehensive transportation policies that not only enhance infrastructure and service quality but also consider environmental perceptions and safety to promote sustainable travel behaviors among university students.
Keywords: travel behavior; mode choice model; sustainable transportation; university students; POSTSECONDARY STUDENTS; CHOICES; PATTERNS; DETERMINANTS; TORONTO; Science & Technology - Other Topics; Environmental Sciences & Ecology